Stability of coupled human and stand-up paddle board - Chen, H.-J.; Sequeira, D.; Mann, B. P. (Sports Engineering, 2018)
This study investigates the rider stability on a stand-up paddle board (SUP) based on board dimensions, rider body parameters, and skill level using a buoyant body dynamics approach. For this study, the system of a rider standing on an SUP is modeled as a planar motion of a rectangular cross-sectional buoyant body with an added mass attached at a fixed height. A stability map is developed to visualize stability regions for various system parameters. The result shows that eigenvalue contours are in good agreement with qualitative terms, such as beginner and professional. A new approach of describing rider skill level is proposed. Wave tank experiments are conducted to verify the analytic equations. Analytical results of the rectangular board show the same trend as the experimental results from a real SUP product.